Calculation of macroparticle flow in filtered vacuum ARC plasma systems - Aksyonov, D.S. (Вопросы атомной науки и техники, 2012)
Model of macroparticle behavior inside plasma guiding channels of vacuum arc systems and program for calculation of macroparticle flow in plasma filters (separators) used in vacuum arc film deposition are described. Several magnetic filters have been modeled to compare calculated and experimental data. The capability of the program to optimize filters is demonstrated on example of straight filter. The high compliance degree of calculated and experimental data is shown.